Gradings induced by nilpotent elements. - García González, Esther; Gómez-Lozano, Miguel Ángel; Muñoz-Alcázar, Rubén José; Vera de Salas, Guillermo (Elsevier, 2023)
An element a is nilpotent last-regular if it is nilpotent and its last nonzero power is von Neumann regular. In this paper we show that any nilpotent last-regular element a in an associative algebra R over a ring of scalars Φ gives rise to a complete system of orthogonal idempotents that induces a finite Z-grading on R; we also show that such element gives rise to an sl2-triple in R with semisimple adjoint map adh, and that the grading of R with respect to the complete system of orthogonal idempotents is a refinement of the Φ grading induced by the eigenspaces of adh. These results can be adapted to nilpotent elements a with all their powers von Neumann regular, in which case the element a can be completed to an sl2-triple and a is homogeneous of degree 2 both in the Z-grading of R and in the Φ-grading given by the eigenspaces of adh.
Keywords: Anillos (Álgebra); Anillos graduados; Von Neumann regular; Nilpotent element; Grading; sl2-triple